Exploring literature and grammar 10 world literature - Hipol, Maria Paula D.J.; Domagsang, Anne Gelene T. (Quezon City. Brilliant Creations Publishing, Inc., 2020)
"This book, Exploring Literature and Grammar 10 (Second Edition), aims to develop the students' communicative competence and multi-literacy in the English language. To achieve the said objectives, the authors have provided exercises (a) to develop the students' communicative competence through understanding of literature and other text types for a deeper appreciation of World Literature including Philippine literature; (b) to improve their understanding of how World Literature serves as a way of expressing and resolving ones' personal conflicts through the use of strategies in linking textual information, repairing or enhancing communication, and crafting formal/informal word definitions; (c) to enable the students to learn the ethics and strategies of public speaking; and use emphasis markers in persuasive texts".
Includes glossary and bibliography.
English text.
Keywords: World Literature